移居高原(4520m)汉族青年男性高尿酸血症发病特点及遗传易感性研究 - Zhong-wei, TANG; Fu-yu, LIU; XU, Gang; Chun-hua, JIANG; Li-bin, GUAN; Qing-yuan, HUANG; Yu-qi, GAO (Jie fang jun yi xue za zhi, 2016)
Objective 　To investigate the pathogenic characteristics of hyperuricemia and the correlation between hyperuricemia and the polymorphism of xanthine oxidase (XO) in young Han males at an altitude of 4520m. Methods 　Two hundred and forty Han Chinese young men, aged 16-36 years (mean 22.1 years), moved to an altitude of 4520m for 0.25-10.8 years (mean 2.3 years), were selected. The general information and physiological index were collected by using questionnaires and routine examination; Fasting venous blood was collected in the morning, serum uric acid and XO concentration were measured, and the rs17038412 polymorphism of XO gene was analyzed. Results 　There were 186 hyperuricemia patients (hyperuricemia group) in 240 subjects, accounting for 77.5%, and 54 people with normal serum uric acid (normal group, accounting for 22.5%). Compared with normal group, the concentrations of XO and hemoglobin were significantly higher, the blood oxygen saturation significantly lower (P<0.01), and blood uric acid concentratio